Perceived organizational politics and quitting plans: an examination of the buffering roles of relational and organizational resources - De Clercq, D. (2021)
Purpose: The goal of this research is to examine the link between employees' beliefs that organizational decision-making processes are guided by self-serving behaviors and their own turnover intentions, as well as how this link may be buffered by four distinct resources, two that speak to the nature of peer exchanges (knowledge sharing and relationship informality) and two that capture critical aspects of the organizational environment (change climate and forgiveness climate). Design/methodology/approach: Quantitative survey data were collected among 208 employees who work in the oil and gas sector in Mozambique. Findings: The results indicate that employees' beliefs about dysfunctional political games stimulate their plans to quit. Yet this translation is less likely to occur to the extent that their peer relationships are marked by frequent and informal exchanges and that organizational leaders embrace change and forgiveness. Practical implications: For organizations, these findings offer pertinent insights into different circumstances in which decision-related frustrations are less likely to escalate into quitting plans. In particular, such escalation can be avoided to the extent that employees feel supported by the frequency and informal nature of their communication with colleagues, as well as the extent to which organizational leaders encourage change and practice forgiveness. Originality/value: This study adds to extant research by explicating four unexplored buffers that diminish the risk that frustrations with politicized decision-making translate into enhanced turnover intentions.